Creation of Music-Induced Analgesia in Chronic Pain Patients through Endogenous Opioid Production: A Narrative Review - Puri Nivriti (International Journal of Pain Management, 2024)
Chronic pain affects over 30% of the global population, and reliance on external drugs for treatment has led to major issues, including the present opioid epidemic. A healthier option is necessary, which is why music therapy’s analgesic effects have been extensively studied within the last 20 years. Not only is music relatively harmless but given that chronic pain patients require repeated treatment, musical intervention is far more accessible and economical. While the mechanisms underlying music-induced analgesia are relatively unclear, the production of endogenous opioids while listening to music through both the descending pain modulatory circuit and the limbic system, is postulated to play this role. This review describes the brain regions and pathways by which music may trigger the release of endogenous opioids such as enkephalins, endorphins, and dynorphins. More importantly, it discusses the cellular mechanisms through which these neuropeptides are thought to mediate pleasure-induced analgesia in chronic pain patients.
Keywords: Chronic pain